Conformationally Altered C-Reactive Protein Capable of Binding to Atherogenic Lipoproteins Reduces Atherosclerosis - Pathak, Asmita; Singh, Sanjay K.; Thewke, Douglas P.; Agrawal, Alok (Frontiers in Immunology, 2020)
The aim of this study was to test the hypothesis that a conformational change in native wild-type C-reactive protein (CRP) is necessary for CRP to prevent the development of atherosclerosis. Atherosclerosis is an inflammatory cardiovascular disease and CRP is a plasma protein produced by the liver in inflammatory states. The co-localization of CRP and atherogenic low-density lipoproteins (LDL) at atherosclerotic lesions suggests a possible role of CRP in atherosclerosis. CRP binds to phosphocholine-containing molecules but does not interact with atherogenic LDL unless the phosphocholine groups in LDL are exposed. However, CRP can bind to atherogenic LDL, without the exposure of phosphocholine groups, if the native conformation of CRP is altered. Previously, we reported a mutant CRP, F66A/T76Y/E81A, generated by site-directed mutagenesis, that did not bind to phosphocholine. Unexpectedly, this mutant CRP, without any more conformational alterations, was found to bind to atherogenic LDL. We hypothesized that this mutant CRP, unlike wild-type CRP, could be anti-atherosclerotic and, accordingly, the effects of mutant CRP on atherosclerosis in atherosclerosis-prone LDL receptor-deficient mice were evaluated. Administration of mutant CRP into mice every other day for a few weeks slowed the progression of atherosclerosis. The size of atherosclerotic lesions in the aorta of mice treated with mutant CRP for nine weeks was ~40% smaller than the lesions in the aorta of untreated mice. Thus, mutant CRP conferred protection against atherosclerosis, providing a proof of concept that a local inflammation-induced structural change in wild-type CRP is a prerequisite for CRP to control the development of atherosclerosis.